Relationship between personal features and copy strategies in joint force participants - Yarmolchyk , Maria; Semenenko , Liliia; Dobrovolskyi , Yuzef; Poberezhec , Tetiana (Social Development and Security, 2021)
The purpose of the article is to study the features of the relationship of personality traits with coping strategies in servicemen who are at the stage of decompression after leaving the combat zone. Researchers’ views on the relationship between coping strategies of behavior with a number of personal characteristics in the military are analyzed. The results of an experimental study of the relationship between the personality traits of servicemen and coping strategies are presented. The following diagnostic tools were used in the study: Questionnaire of self-control methods (adaptation of WCQ method) by R. Lazarus and S. Folkman in adaptation by T. Kryukova, М. Zamyshlyaeva; personal questionnaire "SACS" (S. Hobfall); five-factor personality questionnaire; methods of multifactor study of R. Kettel’s personality; Freiburg personality questionnaire. The following methods were used to process empirical data: descriptive statistics and correlation analysis. The study was conducted with 150 servicemen of the Armed Forces of Ukraine during their decompression operations, after a long stay in the area of ​​the Joint Forces Operation. It is determined that the choice of coping strategies of behavior is determined by personal characteristics. The relationships between indicators of coping strategies and personal traits are established and analyzed: emotional stability and diplomacy, isolation, neuroticism, irritability, reactive aggression, depression, masculinity / femininity, sociability, trust, diplomacy. The use of coping strategies by servicemen during decompression in connection with personal parameters has been proved. Being in difficult conditions undoubtedly affected the psychological characteristics of each soldier. The obtained results contribute to the development of a program for the development of personal determinants of the choice of effective coping strategies of servicemen at the stage of decompression.